Pion, kaon, and proton production in central Pb-pb collisions at √sNN=2.76 TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
In this Letter we report the first results on π±, K±, p, and ¯p production at midrapidity (|y|<0.5) in central Pb-Pb collisions at √sNN=2.76 TeV, measured by the ALICE experiment at the LHC. The pT distributions and yields are compared to previous results at √sNN=200 GeV and expectations from hydrodynamic and thermal models. The spectral shapes indicate a strong increase of the radial flow velocity with √sNN, which in hydrodynamic models is expected as a consequence of the increasing particle density. While the K/π ratio is in line with predictions from the thermal model, the p/π ratio is found to be lower by a factor of about 1.5. This deviation from thermal model expectations is still to be understood.